The Persistence of Corruption and Slow Economic Growth - Mauro, Paolo (IMF Working Papers; Working Paper ;, 2002)
There is increasing recognition that corruption has substantial, adverse effects on economic growth. But if the costs of corruption are so high, why don't countries strive to improve their institutions and root out corruption? Why do many countries appear to be stuck in a vicious circle of widespread corruption and low economic growth, often accompanied by ever-changing governments through revolutions and coups? A possible explanation is that when corruption is widespread, individuals do not have incentives to fight it even if everybody would be better off without it. Two models involving strategic complementarities and multiple equilibria attempt to illustrate this formally.